Metal concentration in ghost shrimp and contamination levels of sandy beaches contrasted with anthropogenic impacts in Southeast Brazil - José-Silva, Juliano [UNESP]; Trevizani, Tailisi H.; Almeida, Alaor A. [UNESP]; Pinheiro, Marcelo A. A. [UNESP] (Springer Nature, 2025)
This study evaluates the contrast in the concentration of seven potentially toxic elements (As, Cd, Cr, Cu, Hg, Mn, and Pb) in tissues (G, gonads; H, hepatopancreas; and M, muscle) of the ghost shrimp Callichirus corruptus, as a response to sediment contamination in two sandy beaches in Southern Brazil with different anthropogenic status (JUR, Juréia; and STS, Santos). The biotic and abiotic samples were collected with a suction pump and subjected to metal quantification by atomic absorption spectrophotometry technique. In JUR, the sediment had Cr, Cu, and Mn concentrations two times lower when compared to STS (t ≤ 7.80; p ≤ 0.01), while STS had Hg concentrations between the Interim Sediment Quality Guideline (ISQG) and probable effect level (PEL) parameters. Three metals (Cd, Cr, and Cu) presented concentrations above the maximum tolerated limit indicated by the Brazilian Health Regulatory Agency (Anvisa), with prawn bioaccumulation up to eight times greater in STS than JUR (t ≥ 4.42; p ≤ 0.03). Therefore, this study confirms higher metal concentrations (μg/g) in the biotic (Cd = 7.86 Cr = 11.95 and Mn = 19.38) and abiotic (Cd = 0.45, Cr = 3.13, Cu = 0.59, Hg = 0.49 and Mn = 45.61) compartments of Santos, which has a high human population density and a significant industrial and port complex, in contrast to Juréia, which is located in a highly conservation ecological station. Furthermore, the research presents novel information on trace elements in the sandy sediments of the studied sites. Additionally, it provides unprecedented evidence on metal concentration for C. corruptus, which can be used in monitoring programs for sandy beaches due to its metal bioaccumulation potential.